(untitled) (Journal of Asian Development Studies, 2025)
Globally, smoking is a significant public health concern that requires innovative cessation interventions. Virtual pharmacist-led programs can provide accessible support, particularly in settings without dedicated services. This study evaluates a virtual pharmacist-led intervention’s impact on smoking cessation, medication adherence, and patient engagement. A quasi experimental pre-post study was conducted in a secondary care hospital in Islamabad, Pakistan, with 80 adult smokers (≥18 years, ≥5 cigarettes/day for a year) willing to quit. The three-month program included weekly teleconsultations, pharmacotherapy guidance, behavioral counselling, and automated text support. Post-intervention, 60% achieved 7-day abstinence (p<0.001). Daily cigarette use decreased from 14.8 ± 5.7 to 6.3 ± 4.2 (p<0.001); nicotine dependence dropped from 6.1 ± 1.9 to 3.2 ± 1.7 (p<0.001). Motivation and medication adherence significantly improved. Logistic regression identified higher motivation, better adherence, and lower nicotine dependence as key predictors. Virtual pharmacist-led interventions show promise in resource-limited settings, warranting further large-scale studies.